Postoperative Treatment With Docetaxel, Cisplatin, and Capecitabine (DCX) and Chemoradiotherapy (CRT) With Capecitabine for Resected Gastric Adenocarcinoma. (February 2015) - Saridaki, Zacharenia; Lambrodimou, Georgia; Kachris, Stefanos; Makrantonakis, Paris; Boukovinas, Ioannis; Polyzos, Aris; Anagnostopoulos, Athanasios; Athanasiadis, Athanasios; Stoltidis, Dimitris; Georgoulias, Vassilis; Souglakos, John
<x xml:space="preserve">Abstract</x> Introduction: We conducted a feasibility study on docetaxel/capecitabine/cisplatin (DCX) with chemoradiotherapy as adjuvant treatment for gastric cancer patients. Methods: Patients were scheduled to receive 2 cycles of DCX, followed by 50.4 Gy plus capecitabine as radiotherapy, followed by an additional 2-DCX cycles. Results: From the 40 enrolled patients, 26 (65%) completed treatment as per protocol and 14 (35%) discontinued with the treatment (patients' refusal: n=6; adverse events: n=8). There were 2 toxic deaths. Grade >3 toxicity was 12.1% before and 13.3% after chemoradiotherapy. Disease progression was documented in 11 (27.5%) patients. Conclusions: No further development of this regimen is justified on the basis of poor tolerability in patients.